HUBUNGAN POLA ASUH ORANG TUA DENGAN KEMANDIRIAN SOSIAL ANAK USIA 4-5 TAHUN DI PAUD ISLAM KECAMATAN SUNGAI RAYA - Sugiyati, Sugiyati; Syukri, M; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstracta.common problem in this study is the relationship of parenting. Parents with the social independence of children aged 4-5 years in the islamic district of the river district.This metlod in the research is de criptive method with gulitative reseach form.the subjects in this study were so student parents in islamic pope sungai raya.Data collection technigues are direct communication technigues and direct observasion.With data collection tools namely interview sheets,observation quidelines,and field notes.the data obtained is then processed and presented in the de sciption of the word throught three stages summarizing or colelleting data, then the data is presented and them dran conclusions.the resullts of interview and observation made show that efforts are being made to improve parenting parents inincreasing the social independence off 4-5 year olds by understandy, interraccting and staying in control, developing potensial, encouraging with skils.Learning patterns of rach student, carry out activities while playing to bring creativity, indepence and critical abiling,focus chidrenâ€™s attention, recognize the type and abiliting of children and establis a conducive relation shipbet wan. His ekpectied that as parents,they should continualy reflect activitas in improving and finding ways or innovations so that children can be independent in relation to their abilities.Â Keywords: Parenting will be the key to growing the child to self reliance.